2016
DOI: 10.5312/wjo.v7.i9.539
|View full text |Cite
|
Sign up to set email alerts
|

Casting: Pearls and pitfalls learned while caring for children’s fractures

Abstract: Casting is a routine procedure used for fracture care in the pediatric population. The purpose of this review is to provide pearls and pitfalls that our institution has learned from previous literature. When applying the cast, we recommend using cotton padding for the liner and fiberglass or plaster depending on how much swelling is expected. A well-molded cast must be applied in order to prevent further fracture displacement. Cast valving is a valuable technique that allows a decrease in pressure which preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 35 publications
0
28
0
1
Order By: Relevance
“…Patients with DRF treated with either of these casts are instructed to keep the cast dry to avoid structural damage and to prevent skin and odor problems associated with excess moisture. 2 , 3 Patients have reported that this places a burden on daily tasks such as showering, bathing, or hand washing. 4 A recent study on a pediatric population has shown that nearly 50% of unplanned cast changes can be attributed to casts getting wet, imposing a clinical and financial burden.…”
Section: Distal Radius Fracture Castsmentioning
confidence: 99%
“…Patients with DRF treated with either of these casts are instructed to keep the cast dry to avoid structural damage and to prevent skin and odor problems associated with excess moisture. 2 , 3 Patients have reported that this places a burden on daily tasks such as showering, bathing, or hand washing. 4 A recent study on a pediatric population has shown that nearly 50% of unplanned cast changes can be attributed to casts getting wet, imposing a clinical and financial burden.…”
Section: Distal Radius Fracture Castsmentioning
confidence: 99%
“…Advances in air ltration, pre-surgical scrub, and surgical site preparation have all played a signi cant role in decreasing surgical site infections [6]. Despite this progress, studies have demonstrated that the vast majority of surgical site contamination in orthopedic surgical procedures is still due to airborne particles settling in the wound or on instrumentation [7]. Minimizing this source of surgical site contamination should be a high priority for improving patient surgical outcomes as well as decreasing risk and cost of procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Según la literatura consultada, se estima que un 0.56% (2) , 15% (3,4) y 38% (5) de niños escayolados sufrirán una úlcera por presión iatrogénica dependiendo de la lesión y el tipo de enyesado, siendo los yesos sintéticos los que desarrollan mayor presión sobre los tejidos (6-8) y generándose dicha úlcera en los primeros días de llevar la inmovilización (9) . La prevención de estos problemas de salud asociados a la inmovilización es una tarea que debe emprenderse por parte de los enfermeros/as que realizan dicho procedimiento con el fin de minimizar los riesgos para la población, no solamente a la hora de realizarla con el mayor rigor científico y profesional, sino reforzando la educación sanitaria a los pacientes en el cuidado de la férula con el fin de prevenir complicaciones (10)(11)(12) .…”
Section: Introductionunclassified